First report of Ophiusa disjungens (Walker, 1858) on Acacia mangium Willd. (Fabaceae), and damage and notes of its biology on Eucalyptus (Myrtaceae) commercial plantations in Sumatra, Indonesia (Lepidoptera: Erebidae) - Raimon, A.; Laksamana, A.; Sinulingga, N. G. H. B.; Ferlianda, I. A.; Samosir, M. N.; Pane, S. B.; Kkadan, S. K.; Tavares, W. de S.; Tarigan, M.; Duran, A. (SHILAP Revista de lepidopterología, 2020)
Acacia mangium Willd. (Fabaceae), Eucalyptus pellita F. Muell. and Eucalyptus grandis W. Hill ex Maiden (Myrtaceae) are largely planted in Sumatra, Indonesia, where they are used as a raw material to produce commodities such as paper, pulp and viscose. Acacia and Eucalyptus are attacked by several species of defoliating Coleoptera and Lepidoptera in Sumatra. The objectives of this study were to report, for the first time, the guava moth, Ophiusa disjungens (Walker, 1858) on A. mangium, and damage and notes of its biology on Eucalyptus commercial plantations in Sumatra. Ophiusa disjungens on six- and seven-month-old A. mangium had an average of three larvae per tree in two commercial stands in Peranap Sector, Riau, Sumatra, on April 2018. The incidence of caterpillars and/or fresh damage (defoliation) of this pest on one-, three- to seven-, nine-, and 10-month old E. pellita and E. grandis ∞ E. pellita ranged 4.0–80.2% within 18 commercial stands in Sei Kebaro Sector, Riau, on April 2020. Caterpillars reared in a laboratory had period from pupa to adult (mean ± SD) of 25.5 ± 4.5 days. Ophiusa disjungens is reported for the first time on A. mangium, and incidence of its caterpillars and/or damage (defoliation) on Eucalyptus is up to 80.2% in Sumatra.